The Relationship Between Pregnant Women's Knowledge of Oral Health Care and Gingivitis at the Karanggeneng Community Health Centre in Lamongan Regency in 2025 - Silviya Anis Sulha; Sunomo Hadi; Ida Chairanna Mahirawatie (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Gingivitis is one of the most prevalent oral health problems among pregnant women, primarily triggered by hormonal changes that increase gingival sensitivity to plaque and local irritants. Despite its high occurrence, inadequate knowledge of oral health care among first-trimester pregnant women (K1) remains a significant concern, potentially worsening gingival conditions and overall maternal health. This study aimed to examine the relationship between pregnant women’s knowledge of dental and oral health maintenance and the incidence of gingivitis at the Karanggeneng Community Health Center, Lamongan Regency. This study employed an analytic survey design with a cross-sectional approach. A total of 37 first-trimester pregnant women were selected using purposive sampling. Data were collected through a structured questionnaire assessing knowledge of oral health care and a clinical examination using the Gingival Index to determine gingivitis status. The relationship between variables was analyzed using Spearman’s rho correlation test. The findings revealed that the majority of respondents had a moderate level of knowledge (54.1%) and experienced moderate gingivitis (62.1%). Statistical analysis demonstrated a significant correlation between knowledge of oral health maintenance and gingivitis status (p = 0.020 < 0.05), indicating that lower levels of knowledge are associated with a higher severity of gingivitis. In conclusion, there is a significant relationship between oral health knowledge and gingivitis among first-trimester pregnant women. Improving knowledge through targeted health education is essential to promote better oral hygiene practices and reduce the risk of gingival inflammation during pregnancy. These findings highlight the importance of integrating oral health education into antenatal care services.